Introduction to Epidemiology - Merrill, Ray M. (Jones & Bartlett Learning, 2013)
This Sixth Edition is a introductory text for the epidemiology student with minimal training in the biomedical sciences and statistics. With updated tables, figures, and examples throughout, the Sixth Edition is a thorough revision that offers an all new, real world examples to help better illustrate elusive concepts. Learning objectives, as well as study questions with descriptive answers, in each chapter engage the student in further analysis and reflection. New Features of the Sixth Edition: Updated tables and figures. Addition of several real-world, practical examples. Added focus on setting-up contingency tables and calculating and interpreting appropriate measures of association. Greater detail and examples on conducting hypothesis testing. Greater detail and examples on calculating age-adjusting rates. Greater detail and examples on calculating years of potential life lost. Greater detail and examples on assessing clinical trials. Updated case studies.